Development and application of multiple immunofluorescence staining for diagnostic cytology of canine and feline lymphoma. (7th December 2015) - Sawa, Mariko; Yabuki, Akira; Setoguchi, Asuka; Yamato, Osamu
Abstract : Background: Immunophenotyping of canine and feline lymphoma to determine B‐cell or T‐cell origin is important for predicting prognosis and for development of treatment protocols. For advanced diagnostic cytology tests that can be performed on smears are required to predict the immunophenotype of lymphomas. Objectives: The aim of this study was to develop a multiple immunofluorescence (MIF) staining method for the determination of lymphocyte immunophenotype in cytologic specimens, and to evaluate its clinical utility. Methods: B cells and T cells were detected using anti‐CD79α and anti‐CD3 antibodies, respectively, followed by specific fluorescence‐labeled secondary antibodies. The MIF staining method was first developed using fresh‐frozen sections of normal canine lymph nodes. The optimal fixative, the necessity of antigen retrieval (AR), and the optimal concentration of the antibodies were determined. The MIF method was then applied to smears of normal lymph nodes, and to clinical samples from dogs and cats with lymphoma. The MIF results were compared to genetic clonality results. Results: B and T cells were detected based on specific fluorescence in frozen sections, using formalin fixation without AR. Specific fluorescence was also detected in smears from normal lymph nodes and lymphomas, and the immunophenotypes predicted from this MIF staining method completely corresponded to those from genetic clonality analysis. Conclusions: The MIF staining method that we developed in this study effectively distinguished lymphocyte immunophenotypes with high specificity and sensitivity using a single smear sample, and was useful as a diagnostic tool for canine and feline lymphoma.